PENGARUH TRANSPARANSI, AKUNTABILITAS, DAN PARTISIPASI MASYARAKAT TERHADAP PENGELOLAAN KEUANGAN DESA (Studi Empiris pada Desa-Desa di Kecamatan Kemuning Kabupaten Indragiri Hilir) - Rahmah, Siti Susanti; Indrawati, Novita; Hariadi, Hariadi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research aims to analyze the effect of transparency, accountability,and community participation on village financial management. This research wascarried out in all villages in Kemuning District, Indragiri Hilir Regency, RiauProvince. The population in this research consisted of 11 villages. The data usedare primary data with questionnaires as instruments. Questionnaires distributedto respondents were 110 people. The data analysis method used in this research ismultiple linear regression analysis using Statistical Product and Service Solution(SPSS) software version 22.0. The results showed that transparency,accountability, and community participation had an influence on village financialmanagement.Keywords : Transparency, Accountability, Community Participation,Management of village finance